Level up: how gamified learning with Kahoot! and Quizizz (Wayground) transforms the English language classroom - Abdul Mutalib, Nor Adriena Amiz; Bazlan, Anis Shahira (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Gamified learning platforms like Kahoot! and Quizizz (now Wayground) are transforming language classrooms by actively engaging students through game-based elements such as points, challenges, and instant feedback. Instead of passive memorisation, learners become motivated participants who connect with content, collaborate, and build essential soft skills. These tools not only enhance English language acquisition but also foster curiosity, adaptability, and resilience key qualities that support lifelong learning in an evolving educational landscape.